68 and FX2149 Attenuate Mutant LRRK2-R1441C-Induced Neural Transport Impairment - Thomas, Joseph M.; Li, Tianxia; Yang, Wei; Xue, Fengtian; Fishman, Paul S.; Smith, Wanli W. (Frontiers in Aging Neuroscience, 2017)
Leucine-rich repeat kinase 2 is a large protein with implications in genetic and sporadic causes of Parkinson’s disease. The physiological functions of LRRK2 are largely unknown. In this report, we investigated whether LRRK2 alters neural transport using live-cell imaging techniques and human neuroblastoma SH-SY5Y cells. Our results demonstrated that expression of the PD-linked mutant, LRRK2-R1441C, induced mitochondrial and lysosomal transport defects in neurites of SH-SY5Y cells. Most importantly, recently identified GTP-binding inhibitors, 68 and FX2149, can reduce LRRK2 GTP-binding activity and attenuates R1441C-induced mitochondrial and lysosomal transport impairments. These results provide direct evidence and an early mechanism for neurite injury underlying LRRK2-induced neurodegeneration. This is the first report to show that LRRK2 GTP-binding activity plays a critical role during neurite transport, suggesting inhibition of LRRK2 GTP-binding could be a potential novel strategy for PD intervention.